BIOPOTENCY OF MACA (Lepidium meyenii) POWDER SUPPLEMENTATION ON PERFORMANCE AND HAEMATOLOGICAL PROFILE OF YANKASA RAMS DURING HOT SEASON (FUDMA JOURNAL OF SCIENCES, 2025)
Evaluation of hematological profile of Yankasa rams is a vital indicators of animal health, nutritional, welfare, physiological and pathological condition assessment therefore, this study was specifically designed to evaluate the effect maca (Lepium meyenii) powder supplementation on serum biochemistry of Yankasa rams raised during hot season. A total of 20 pubertal Yankasa rams were divided into four treatment groups of 0, 5, 10, 15g/ Kg powdered maca per kg diet with five (5) rams each per treatment in a Completely Randomized Design (CRD). At the end of experiment blood samples were collected and analyzed for hematological and red blood cell abnormality. Data obtained were analyzed using analysis of variance of statistical analysis system were treatment means were separated using Duncan Multiple Range Test (DMRT). The result showed that there were significant (P0.05). Haematological profile of Yankasa rams supplemented maca have greatly showed significant (P0.05) differences in this study. Among the red blood abnormalities T1 had moderate elliptocytes, rouleux, and acanthocytes with presences of anisocytosis, hypochromia, poikilocytes and microcytosis while other treatment groups contain either slight, presence or absent of red blood cells abnormality. It could therefore concluded that supplementation of maca powder at 10 and 15g/kg had an outstanding growth performance and haematological profile within the reference range.
Keywords: Growth; Haematology; Maca; Yankasa Rams